The "Home Advantage" in Athletic Competitions. (February 2014) - Allen, Mark S.; Jones, Marc V.
Game location has a powerful influence on performance outcomes in sport. We reviewed recent research on three conceptual models that outline (a) the various game-location factors that can alter athletes' psychological states, (b) the natural protective response to territorial incursion in humans, and (c) the increased probability of involuntary attentional shifts in the presence of a supportive audience. Investigators recently have accumulated support for each of these models and linked variations in game location to psychological, hormonal, and behavioral states of athletes, coaches, and officials. We considered how an integrative approach might benefit the study of the home-advantage phenomenon and described an assortment of research questions to support the development of an integrative framework. By studying how audience support contributes to physiological reactivity, attention, stress responses, and decision making (among athletes and officials), researchers can achieve a better understanding of the processes through which a home environment can benefit (and occasionally harm) athletes and teams.